A Semi-Empirical and Density Functional Theory Study of 2,2’,3,4-Tetrahydroxy-3’- sulpho Azobenzene Derivatives and Their Zirconium Complexes - Uysal, U.D. (Asian Journal of Chemistry, 2012)
In this study, certain theoretical properties of three tetrahydroxyazo derivatives and their zirconium complexes, such as stability, reactivity, geometry and energy have been calculated by MOPAC2009 with the PM6 method and GAUSSIAN 09 programs at the basis set B3LYP/ LanL2DZ to understand the basic principles concerning their behaviour. The theoretical data was then compared with that of certain experimental results realized earlier by our group to ascertain any possible correlation.